INNOVATIVE SOLUTION FOR BIOGAS PRODUCTION - Saloydinov Sardorjon Qodirjon o'g'li (Research Focus International Scientific Journal, 2022)
The article presents the rationale for the relevance, scientific novelty and practical significance of the proposed control system for a multi-chamber reactor. Variants of comparison with similar foreign solutions are proposed